2017
DOI: 10.1186/s12884-017-1503-5
|View full text |Cite
|
Sign up to set email alerts
|

The design and implementation of an obstetric triage system for unscheduled pregnancy related attendances: a mixed methods evaluation

Abstract: BackgroundNo standardised system of triage exists in Maternity Care and local audit identified this to be problematic. We designed, implemented and evaluated an Obstetric Triage System in a large UK maternity unit. This includes a standard clinical triage assessment by a midwife, within 15 min of attendance, leading to assignment to a category of clinical urgency (on a 4-category scale). This guides timing of subsequent standardised immediate care for the eight most common reasons for attendance. A training pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…Mistry reported a similar perception among nurses in the United Arab Emirates [40]. Grading criteria in all existing obstetric triage is severity and acuity of disease [8,23,41].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Mistry reported a similar perception among nurses in the United Arab Emirates [40]. Grading criteria in all existing obstetric triage is severity and acuity of disease [8,23,41].…”
Section: Discussionmentioning
confidence: 75%
“…Time to visit doctors is set almost in all types of general triage (ATS, CTAS, MTS, and ESI) [36,[44][45][46]. In this regard, different obstetric triages also follow the principles of general triage based on which they are designed [20,41,47].…”
Section: Discussionmentioning
confidence: 99%
“…Mistry reported a similar perception among nurses in the United Arab Emirates [ 40 ]. Grading criteria in all existing obstetric triage is severity and acuity of disease [ 8 , 24 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Time to visit doctors is set almost in all types of general triage (ATS, CTAS, MTS, and ESI) [ 36 , 45 – 47 ]. In this regard, different obstetric triages also follow the principles of general triage based on which they are designed [ 21 , 41 , 48 ]. Since triage aims to provide the right treatment at the right time, it seems necessary to determine the appropriate schedule for assessment and evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Obstetric departments in high income settings have been slower to adopt a formal structure, despite this being identified as an area for improvement (Macones et al, 2016;Angelini and Howard, 2014). A large UK survey in 2015 suggested that 81% of hospitals do not have a formal obstetric triage system in place (Kenyon et al, 2017). Recently, some maternity units have been adopting a more formal approach, with good results (Kenyon et al, 2017;Ruhl et al, 2015;Quaille, 2018;Humphrey et al, 2017;Paisley et al, 2011;Smithson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%